Battle of the bands: a long-term analysis of frequency band and channel distribution development in WLANs - Lindroos Saku; Hakkala Antti; Virtanen Seppo (Institute of Electrical and Electronics Engineers, 2022)
In this article, we present the results of a long-term analysis ofWireless Local Area Network (WLAN) frequency band and channel distribution development. To the best of our knowledge, no similar research has been published in recent academic publications. Overcrowding of the limited frequency space on the 2.4 GHz band has become a significant issue in WLAN networking. Due to the overabundance of devices operating at 2.4 GHz, avoiding network performance degrading interference has become impossible in densely populated environments. Although the latest 802.11 WLAN standard amendments have shifted their emphasis toward the wider and less congested 5 GHz band, the 2.4 GHz band has stayed as the dominant frequency band. To observe the evolvement of WLAN frequency band and channel utilisation, data collected on nine WLAN surveys conducted between May 2019 and January 2022 was analysed. Furthermore, a simple linear regression model was produced to forecast the future development of WLAN frequency band utilisation. It was hypothesised that there would be an increase in 5 GHz frequency band utilisation as devices compliant with the latest 802.11 standard amendments become widely adopted. The survey results show a significant increase in 5 GHz frequency band utilisation. While the number of networks operating at 2.4 GHz saw a modest 42% increase, the number of networks operating at 5 GHz over doubled during the survey period. At the end of the study, 35% of all detected networks operated at 5 GHz, compared to 25% at the beginning of the study. Based on the produced linear regression model, the portion of 5 GHz networks in the survey area is expected to reach the level of 2.4 GHz networks by the autumn of 2025.